ANALISIS SCP (Structure, Conduct and Performance) PASAR OJOL DI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Widia Wati; Novia Dewi; Jum'atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Marketing ojol in Kampar Kampar Kiri inefficient, resulting ojol price is determined by the merchant. This study aims to identify marketing channels know the structure, behavior and market performance. The study was conducted in the village of Kuntu and Uncle Bay Village East and purposively selected using survey methods. Farmer respondents were chosen randomly and were taken all marketing agencies involved in marketing ojol. Marketing channels described descriptively. The market structure described in descriptive (number of market participants and the barriers and out of the market) and quantitative (calculating the concentration ratio, market share and index Herfindhal). Market conduct is described by descriptive (collusion and tactics performed and pricing practices) and quantitative (calculating correlations and price transmission elasticity). Performance markets analyzed quantitatively (compute marketing margins, share prices, costs and profits). Results of research in Kampar Kiri shows (1) the majority of farmers use marketing channels I; (2) market structure that occur are imperfectly competitive market, as indicated by the results of the analysis of the concentration ratio, market share and index Herfindal and by looking at the number of market participants and the obstacles out of the market; (3) ojol market conduct that occurs is not perfectly competitive market, which is shown from the results of correlation analysis, price transmission elasticity, collusion and tactics performed and pricing practices; and (4) the performance ojol market is not efficient, visible from the calculation of the margin, share costs and profits are large and uneven, share price received by farmers is lower. Keywords: Channels, Structure, Conduct, Performance of Market